Biodiversity of Sciaridae (Diptera) in Ukraine - A. I. Babytskiy; Безсмертна, Олеся Олексіївна; Проценко, Юрій Валерійович; S. D. Pavliuk; N. V. Rubanovska (Дніпровський національний університет імені Олеся Гончара, 2022)
Sciarids (Diptera, Sciaridae) or black fungus gnats are small, mainly dark coloured insects whose larvae usually develop in rotting plant remains permeated by fungal hyphae. Typical habitats for sciarids are shaded forests and wet meadows, but some species can migrate from natural biotopes to anthropogenic ecosystems and live as synanthropes. We have investigated ecological and chorological features of sciarids in Ukraine since 2012. Within this work, we collected imagoes during expeditions and excursions in different biotopes using the Malaise trap, by the method of sweeping and with exhauster directly from substrate. Collected imagoes were placed into 5 mL vials with 70% ethanol. In the lab fixed material was dehydrated in absolute ethanol and mounted on the slides in Euparal. Previous registrations are based on 6 field collections, two of them were carried out in the XIX century, 4 observations of “army worms” and two pest records. From published material of these collections 78 sciarid species were known from 17 genera in 8 more or less specified localities of Ukraine. Our sciarid study in the country expanded the data on registered sciarids by adding 18 new species and enriched information about the distribution of sciarids by 86 new findings of previously known species in 12 regions (Volyn, Cherkasy, Chernihiv, Ivano-Frankivsk, Kharkiv, Khmelnytsk, Kyiv, Lviv, Odesa, Poltava, Rivne and Ternopil) of Ukraine. The current checklist of Sciaridae of Ukraine contains 96 species from 17 genera in 168 localities. Through comparison with Germany, whose sciarid fauna is studied much better, for Ukraine we can predict the presence approximately 400 sciarid species, so the species diversity of Sciaridae in Ukraine still poorly known for the known species does not exceed 25 percent of presumed existing species here. The majority of sciarid findings are registered in different types of broadleaf forest biotopes, only a few species have been found also in grassland habitats. Some sciarid species show synanthropic attraction and have been registered in anthropogenic habitats, for example Bradysia fenestralis (pest of cultivated plants in greenhouses), Corynoptera dentiforceps, Scatopsciara atomaria and Corynoptera tridentata. Larvae of Bradysia placida develop in rotten wood, also development of Corynoptera membranigera preimaginal phases possibly takes place in the fruit bodies of fungi (Neoboletus luridiformis, Russula sp.) and Mycetozoa (Fuligo septica).
Keywords: Sciaroidea; black fungus gnats; species diversity; distribution